Contractors' Perspective on Material Waste Reduction in Kuala Lumpur - Nurul Aini, Osman; M.A., Shazwan; Pok, Jye Hwoi (2016)
Construction waste is considered as one of the significant issue in the sustainable development area. It is responsible for producing a whole assortment of waste, depending on factors either it is at the stage of construction, type of construction work and practices on site. This paper focusing on the research to assess the level of contribution of some waste minimization measures to waste reduction and the level of practice of such measures in the Kuala Lumpur construction industry. A structured questionnaire survey was conducted to extract contractors’ views on twenty five waste minimization measures that adopted from several literatures. The data were obtained and analyzed by using frequency analysis method and average index analysis method. The results showed that out of twenty five waste minimization measures, adoption of proper site management techniques is highly practiced. The findings from the study present the Kuala Lumpur construction industry with measures which expressively contribute to materials waste minimization on construction sites. The adoption of these waste minimization measures could produce great cost savings to the construction industry and prevent environmental degradation.